The Path Toward PET-Guided Radiation Therapy for Glioblastoma in Laboratory Animals: A Mini Review - Donche, Sam; Verhoeven, Jeroen; Descamps, Benedicte; Bolcaen, Julie; Deblaere, Karel; Boterberg, Tom; Van den Broecke, Caroline; Vanhove, Christian; Goethals, Ingeborg (Frontiers in Medicine, 2019)
Glioblastoma is the most aggressive and malignant primary brain tumour in adults. Despite the current state-of-the-art treatment, which consists of maximal surgical resection followed by radiation therapy, concomitant and adjuvant chemotherapy, progression remains rapid due to aggressive tumour characteristics. Several new therapeutic targets have been investigated using chemotherapeutics and targeted molecular drugs, however, the intrinsic resistance to induced cell death of brain cells impede the effectiveness of systemic therapies. Also, the unique immune environment of the central nervous system imposes challenges for immune-based therapeutics. Therefore, it is important to consider other approaches to treat these tumours. There is a well-known dose-response relationship for glioblastoma with increased survival with increasing doses, but this effect seems to cap around 60 Gy, due to increased toxicity to the normal brain. Currently, radiation treatment planning of glioblastoma patients relies on CT and MRI that does not visualize the heterogeneous nature of the tumour, and consequently, a homogenous dose is delivered to the entire tumour. Metabolic imaging, such as positron-emission tomography, allows to visualize the heterogeneous tumour environment. Using these metabolic imaging techniques, an approach called dose painting can be used to deliver a higher dose to the tumour regions with high malignancy and/or radiation resistance. Preclinical studies are required for evaluating the benefits of novel radiation treatment strategies, such as PET-based dose painting. The aim of this review is to give a brief overview of promising PET-tracers that can be evaluated in laboratory animals to bridge the gap between PET-based dose-painting in glioblastoma patients.